THE PROBLEMS OF WRITING RECOUNT ENCOUNTERED BY STUDENTS OF THE STATE JUNIOR HIGH SCHOOL 2 PURWOREJO IN THE ACADEMIC YEAR 2009/2010 (Universitas Negeri Semarang, 2011)
Writing is a skill for the students to express their ideas in written form thatinvolves the mastery of all elements in the target language: as grammar,content, organization, vocabulary, punctuation, spelling and mechanics. Itneeds a complex process. Consequently, the students may have difficultiesto do so.The objectives of my study are to find out how the communicativepurpose of a recount text written by the students is achieved, how recounttexts written in terms of functional stages, the features of lexico -grammatical problems, and to explain why the students write recount text inthe way they do. The problems of the study are therefore: how is thecommunicative purpose of recount texts written by the students of